Inclusive Education and Disability through Active Participation: Action Research and the Implementation of the Perkins Model Program in Three Latin America Countries (Papeles, 2025)
Introduction: This paper presents the analysis of an experience developed through the interrelation of a well-established educational action strategy, the implementation of the Model Program Approach (MPA) promoted by Perkins School for the Blind, and a systematic process of participatory action research. This combination enabled the development of situated knowledge grounded in school practices. The research was conducted between 2023 and 2025 across 27 regular schools, special education schools, and early childhood centers in Argentina, Brazil, and Mexico, using collaborative qualitative methodologies and institutional self-assessment tools. Methodology: To collect information, semi-structured interviews, focus groups, participatory and non-participatory observation records, field notes on the monitoring of implemented change actions, analysis of school documents, and the annual application of the Perkins Quality Indicators were used. Results and Discussion: The results show significant progress in the participation of students with visual impairments, multiple disabilities, and deafblindness, as well as in professional development of teachers, active family involvement, and the consolidation of sustainable inclusive practices. Conclusions: This experience not only allowed for collective documentation and reflection on the ongoing transformations but also offered meaningful insights to strengthen more just, contextualized, and transformative educational systems in Latin America.
Keywords: Inclusive education; pedagogical research; innovation; special education; social inclusion